Evolving consensus around Moroccan-Israeli normalisation: a political space analysis - Alfonso Casani; Francesco Colin (L’Année du Maghreb)
Morocco’s accession to the Abraham Accords in December 2020 represented a shift in the country’s long-standing diplomatic position regarding the Palestinian cause. Remarkably, this shift challenged the accepted political consensus on this issue, forcing a repositioning of actors and opening possible spaces for counter-narratives. In doing so, it also provoked wide social mobilizations, which included the transversal participation of broad sectors of Morocco’s society. This contribution looks at the consequences of the shifting consensus on Palestine through the analytical framework of political spaces, understood as arenas of conflict and cooperation for the negotiation of consensus. The paper argues that this rupture of the accepted consensus created a new cleavage in Morocco’s society. On one hand, most political parties accepted this turning point in Morocco’s diplomatic position, echoing the diplomatic and economic benefits resulting from this change. On the other, this decision revitalized the advocates for the Palestinian cause, mainly gathered around the “National Front in Support of Palestine and Against Normalization”. Ultimately, this paper offers insights on the way in which state and society shape political consensus, as well as on the ways in which they interact and compete to impose their narrative.